MOLECULAR SCALE INVESTIGATIONS OF THE REACTIVITY OF MAGNETITE WITH FORMIC ACID, PYRIDINE, AND CARBON TETRACHLORIDE - Cutting R.S.; Vaughan D.J.; Muryn C.A.; Thornton G. (My University, 2006)
The (111) surface of magnetite, a dominant growth and fracture surface of this mineral, has been studied using Scanning Tunneling Microscopy (STM) at atomic resolution. In line with previous work, this surface shows three possible terminations which can be related to different level slices through the bulk structure. The reactivities of these different surface terminations have been explored by exposing them, under highly controlled conditions, to formic acid, pyridine, and carbon tetrachloride and undertaking further imaging at atomic resolution. These investigations have, themselves, helped to discriminate between competing models of surface structure. The so-called A′ surface termination we now regard as exposing 1/4 monolayer of tetrahedrally coordinated Fe ions over a close packed oxygen layer, and the A surface termination as being these same Fe ions but each capped by a single oxygen. The so-called B surface termination, previously thought to expose 1/2 monolayer of equal numbers of octahedral and tetrahedral Fe ions over a close packed oxygen layer, we now regard as this same arrangement but again with each Fe capped with an oxygen. For all three molecules, the A′ surface is most reactive but the reactions observed are markedly different. Formic acid undergoes dissociation at the magnetite surface, apparently chemisorbing at the A′ surface via a bidentate non-bridging complex. On the same A′ surface, pyridine is chemisorbed through a monodentate linkage via the 'basal' nitrogen of the molecule. For both formate and pyridine, a weaker interaction (a 'physisorption') was observed with the A and B surfaces, interpreted as involving attachment of the intact molecule. The exceptions to this were where the interaction involved chemisorption at defects on A and B type surfaces. The behavior of carbon tetrachloride on the magnetite surface is very different to the other molecules studied. Only the A′ surface is significantly reactive, and the molecule undergoes a series of temperature-dependant dissociation and surface chemical reactions. These involve sorption of intact CCl4 molecules at the lowest temperatures, dissociation into CCl2 and Cl species at around room temperature, and removal from the magnetite of surface oxygens to form OCCl2 and then Fe to form FeCl2 at successively higher temperatures. At around room temperature, both strongly bonded Cl atoms and weakly bonded CCl2 molecules appear to co-exist on the same (A′ type) surface, a situation not previously observed in iron oxide systems. © 2006 Elsevier Inc. All rights reserved.